2018
DOI: 10.3390/ijms19010265
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Promoters from Three Subtypes of the PI3K Family and Their Roles in the Regulation of Lipid Metabolism by Insulin in Yellow Catfish Pelteobagrus fulvidraco

Abstract: In the present study, the length of 360, 1848 and 367 bp sequences of promoters from three subtypes of PI3K family (PI3KCa, PI3KC2b and PI3KC3) of yellow catfish Pelteobagrus fulvidraco were cloned and characterized. Bioinformatics analysis revealed that PI3KCa, PI3KC2b and PI3KC3 had different structures in their core promoter regions. The promoter regions of PI3KCa and PI3KC2b had CpG islands but no CAAT and TATA box. In contrast, the promoter of PI3KC3 had the canonical TATA and CAAT box but no CpG island. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
(78 reference statements)
1
7
0
Order By: Relevance
“… 36 , 44 HNF-1 countered STAT phosphorylation and the expression of DPP4/NOX1, ameliorating the oxidative function of mitochondria and hepatocellular lipid decomposition, which hindered hepatic lipidosis and the progression of NAFLD. 1 , 2 , 6 , 56 , 57 Moreover, the deletion of HNF-1α/HNF-1β accelerated the synthesis of fatty acids and hepatic fat accumulation to boost the development of NAFLD in C57BL/6J mice. HNF-1β overexpression remarkably decreased hepatic lipid accumulation in both HF diet-fed mice and db/db mice.…”
Section: Hnf-1 In Lipid Disordersmentioning
confidence: 99%
“… 36 , 44 HNF-1 countered STAT phosphorylation and the expression of DPP4/NOX1, ameliorating the oxidative function of mitochondria and hepatocellular lipid decomposition, which hindered hepatic lipidosis and the progression of NAFLD. 1 , 2 , 6 , 56 , 57 Moreover, the deletion of HNF-1α/HNF-1β accelerated the synthesis of fatty acids and hepatic fat accumulation to boost the development of NAFLD in C57BL/6J mice. HNF-1β overexpression remarkably decreased hepatic lipid accumulation in both HF diet-fed mice and db/db mice.…”
Section: Hnf-1 In Lipid Disordersmentioning
confidence: 99%
“…At present, the underlying transcriptional mechanism of PI3KC3 was still little known in sh. Our previous study have isolated partial promoter sequence of pi3kc3 from yellow cat sh and have founded that FOXO1 positively regulated the transcription of pi3kc3 (Zhuo et al 2018). However, whether the transcription of pi3kc3 could be regulated by the transcript factors of STAT3, PPARα and PPARγ was not studied due to the short length of pi3kc3 promoter sequence we have obtained.…”
Section: Discussionmentioning
confidence: 98%
“…Hepatocytes were isolated from yellow cat sh according to our previous studies and were cultured in M199 medium containing 1 mmol/L L-glutamine, 5% (v/v) FBS, penicillin (100 IU/mL) and streptomycin (100 g/mL) in a humidi ed atmosphere with 5% CO 2 at 28°C (Zhuo et al 2018). Hepatocytes were counted using a hemocytometer based on the trypan blue exclusion method and only more than 95% cell viability were used for the present experiment.…”
Section: Exp2 Fa Incubation With Hepatocytes Of Yellow Cat Shmentioning
confidence: 99%
“…Zhuo et al ( 55 ) reported that oxidative stress is the primary cause of cancer and inflammation, amongst other diseases. In prostatitis, numerous inflammatory factors are released in response to local inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%